Setting the Climate for Evidence-Based Nursing Practice: What Is the Leader's Role? - Sonia A. Udod and W. Dean Care (Nursing Leadership, 2004)
Nurses are being challenged today to justify their practice. Many clinical and policy decisions in nursing are based upon isolated, ritualistic and unsystematic forms of clinical practice. The growing movement towards establishing evidence-based nursing practice (EBNP) is situated in a systematic appraisal of the best evidence available. Nurse leaders have an obligation to cultivate sound clinical and economic practices leading to quality patient care and positive work life environments for nurses.